Beckman Immunochemistry Analyzer
Beckman Instruments debuted an Immunochemistry Analyzer in 1977 and an Auto ICS (Immunochemistry System) in 1980.
Keywords: Immunochemistry; Scientific apparatus and instruments; Beckman Instruments, Inc.